Empirical Analysis of the Portfolio Theory - Yang, Rui (Transactions on Economics, Business and Management Research, 2024)
As financial markets expand rapidly, investors face complex challenges while pursuing high returns. Therefore, it is necessary for investors to have knowledge of investment theory so that they can take a more rational approach to the actual investment process and decision-making. Portfolio theory, proposed by Markowitz, emphasizes the reduction of risk through diversified investment and becomes the basis of modern financial theory. This paper introduces the basic principles and assumptions of portfolio theory and shows how to apply this theory to portfolio optimization in Excel. Three stocks, Tesla (TSLA.O), Mediea Group (000333.SZ) and Wuliangye (000858.SZ), were selected as examples in this research. It is found that the Markowitz model performs well in reducing risk and increasing the Sharpe ratio, but there are problems with high computational complexity and ideal assumptions in practice. It can be found that portfolio theory plays a key role in asset allocation and risk management, providing some reference for investors and improving direction for future research.